2015
DOI: 10.1007/s10158-015-0180-1
|View full text |Cite
|
Sign up to set email alerts
|

Decrease in levels of the evolutionarily conserved microRNA miR-124 affects oligodendrocyte numbers in Zebrafish, Danio rerio

Abstract: Oligodendrocytes produce multi-lamellar myelin membranes that surround axons in the central nervous system (CNS). Preservation and generation of myelin are potential therapeutic targets for dysmyelinating and demyelinating diseases. MicroRNAs (miRNAs) play a vital role in oligodendrocyte differentiation and overall CNS development. miR-124 is a well-conserved neuronal miRNA with important roles in neuronal differentiation and function. miR-124 levels increase following loss of myelin in both human and rodent b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…Increasing miR-124 expression in the brain of mice subjected to stroke via intravenous injection of miR-124 agomir significantly decreases infarct volume and attenuates neuronal cell death and late apoptosis [ 53 ]. Loss ofmiR-124decreases oligodendrocyte cell numbers and myelination of axonal projections in the ventral hindbrain [ 54 ]. In this study, we found that D-4F significantly increases miR-124a expression and decreases its target gene MMP9, TLR4 and TNFα, while promoting M2 macrophage polarization in the ischemic brain and in cultured PCN and microglia cells subjected to high glucose and OGD conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing miR-124 expression in the brain of mice subjected to stroke via intravenous injection of miR-124 agomir significantly decreases infarct volume and attenuates neuronal cell death and late apoptosis [ 53 ]. Loss ofmiR-124decreases oligodendrocyte cell numbers and myelination of axonal projections in the ventral hindbrain [ 54 ]. In this study, we found that D-4F significantly increases miR-124a expression and decreases its target gene MMP9, TLR4 and TNFα, while promoting M2 macrophage polarization in the ischemic brain and in cultured PCN and microglia cells subjected to high glucose and OGD conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the loss of miR-124 led to decreased axonal projections and MBP+ oligodendrocytes in the zebrafish hindbrain, which is likely an indication that axonal-glial interactions play a role in oligodendrocyte development (Morris et al, 2015).…”
Section: Mirnas In Oligodendroglial Specificationmentioning
confidence: 98%
“…Increased levels of miR‐124 are also associated with demyelination of the hippocampus in human MS samples and the cuprizone mouse model of demyelination (Dutta et al, 2013). Interestingly, the loss of miR‐124 led to decreased axonal projections and MBP+ oligodendrocytes in the zebrafish hindbrain, which is likely an indication that axonal‐glial interactions play a role in oligodendrocyte development (Morris et al, 2015).…”
Section: Regulation Of Oligodendrocyte Development and Myelinationmentioning
confidence: 99%
“…This finding adds further complexity to the roles of miRNAs in myelin biology, as demyelination results in altered neural miRNA expression and subsequent function as a result of miRNA dysregulation. Furthermore, loss of miR-124 in zebrafish development resulted in reduced MBP + cell numbers, likely due to the indirect influence of miR-124 on neurons and disruption of axonal-glial signals and cross-talk that are required for proper OL maturation and myelination (Morris et al, 2015 ).…”
Section: Mirnas As Key Regulators Of Oligodendrocyte Developmentmentioning
confidence: 99%